STRATEGI MEMBANGUN GENERASI BERAKHLAK MELALUI PENDEKATAN PENDIDIKAN ISLAM DI LINGKUNGAN SEKOLAH - Nabila, Kamelia; Yusuf, Budi; Rohman, Taufikur (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2024)
Moral education in schools is very important in forming the character of the younger generation who have morals and integrity. Building morals includes developing good values, with the aim of creating intelligent, emotional and spiritual individuals. Teachers and parents have a crucial role in this process. Islamic education in schools provides a strong framework for moral formation through a values-based curriculum, character education, and a supportive environment. It is hoped that these strategies will be able to form a generation that not only excels academically, but also has noble morals, which are the main pillars in building a harmonious and prosperous society.